HIV Investment in Togo : Optimizing Investments for a Sustainable and Efficient HIV Response in Togo - World Bank (World Bank, Washington, DC, 2019)
This report summarizes the findings of an allocative efficiency analysis of Togo’s HIV response. The Government of Togo indicated a desire to mobilize additional resources, including domestic and private resources, for comprehensive HIV services to respond to the goals of the national HIV Strategic Plan. To ensure that the resources that have been, or will be, mobilized are used in the most efficient way, and to determine the allocation of resources that brings the greatest health benefit, the Government of Togo asked the World Bank to conduct an allocative efficiency analysis using the Optima HIV mathematical model. The findings highlighted a significant treatment gap, and argue strongly for additional funding to scale up ART and increase coverage, in particular for key populations. In order to reduce incidence and deaths by 50 percent, resources should be shifted from prevention programs targeting the general low risk population to ART, PMTCT, and non-ART prevention programs targeting key populations.